Nghiệm của phương trình \(2\cos x - \sqrt 3  = 0\) là:
A.\(\left[ \begin{array}{l}x = \frac{\pi }{6} + k2\pi \\x = \frac{{5\pi }}{6} + k2\pi \end{array} \right.\,\,\left( {k \in \mathbb{Z}} \right)\)
B.\(\left[ \begin{array}{l}x = \frac{\pi }{3} + k2\pi \\x = \frac{{2\pi }}{3} + k2\pi \end{array} \right.\,\,\left( {k \in \mathbb{Z}} \right)\)
C.\(x =  \pm \frac{\pi }{3} + k2\pi \,\,\left( {k \in \mathbb{Z}} \right)\)
D.\(x =  \pm \frac{\pi }{6} + k2\pi \,\,\left( {k \in \mathbb{Z}} \right)\)

Các câu hỏi liên quan